Design of a conceptual model for a maintenance object within a producer: impact on distribution network - a simulation case study. Issue 1 (October 2021) - Gejo, J; Gallego, S; García, M
Abstract: Nowadays, logistics can be described as an interdisciplinary strategy to optimize the production system. Availability is, therefore, the link between logistics and industrial maintenance. To manage this paradigm, maintenance management for a production process plays a key role. Therefore, the purpose of this paper is to design a holistic process-oriented approach to assess the impact of maintenance management on the distribution network and end-customer. As a result, impacts and interrelationships between maintenance and distribution towards the end-customers are derived. Based on the conceptual model, a simulation case study in a supply chain with a producer and its distribution network is developed. Goal is to observe the results of a certain maintenance strategy and its related maintenance characteristics in the subsequent steps of the production process and in the end-customer through the distribution network. The analysis of the case study is performed by means of simulation. The simulation model is built using System Dynamics (SD). Thanks to the scenarios and their results the impact of the maintenance strategy of one object could be observed. The impact depends also on other factors than only maintenance of the object such as customer demand, stocks, supply chain steps and proximity to end-customers.